A synthetic optimization study on thermoresponsive core cross-linked starpolymers (CCSs) - Je Kwon, Young; Seo, Jin Young; Kim, Hun Se; Sharma, Yamini; Shon, MinYoung; Vivek, E.; Cho, Sangho; Baek, Kyung Youl; Cho, Kie Yong (Elsevier BV, 2023)
The well-defined starpolymers can offer a precise stimuli-responsive drug delivery system (SDDS). For this, core cross-linked starpolymers (CCSs) using the poly(N-isopropylacrylamide)-b-poly(n-butyl acrylate) (PNB) linear arm chain and ethylene glycol diacrylate (EGDA) cross-linker were designed and synthesized by the reversible addition-fragmentation chain transfer (RAFT) system. The important synthetic parameters, including reaction time, radical concentration, and cross-linker concentration, were varied to optimize the reaction conditions for highly uniform PNiPAM-based amphiphilic starpolymers (PNBA). The reaction was monitored by GPC, resulting in the sharp monomodal PNBA GPC curve with an almost degraded original curve corresponding to the PNB linear chain. The PNBA revealed a dramatic size increase from 150 nm to 15,000 nm when the temperature increased up to 40 °C. Notably, the uniform CCS structure gives rise to a particular phase transformation system, which can be helpful in biomedical and catalytic applications with enhanced performance.